Encapsulation of tissue plasminogen activator in pH-sensitive self-assembled antioxidant nanoparticles for ischemic stroke treatment – Synergistic effect of thrombolysis and antioxidant –. (September 2019) - Mei, Ting; Kim, Ahram; Vong, Long Binh; Marushima, Aiki; Puentes, Sandra; Matsumaru, Yuji; Matsumura, Akira; Nagasaki, Yukio
Abstract: The medical treatment for stroke has advanced greatly in recent years. Thrombolytic therapy with tissue plasminogen activator (t-PA) is one of the mainstream treatments, but it still has many problems, including short half-life, and t-PA-induced reperfusion and oxidative injuries. To broaden the therapeutic window of t-PA and reduce its associated oxidative stress after reperfusion, t-PA-installed, nitroxide radical-containing, self-assembled polyion complex nanoparticles (t-PA@iRNP) were designed. Encapsulation of t-PA in the self-assembled antioxidant nanoparticles improved its bioavailability and extended its therapeutic window. To suppress reactive oxygen species (ROS) in the ischemic penumbra area, the low-molecular-weight nitroxide antioxidant 4-amino-2, 2, 6, 6-tetramethylpiperidine-1-oxyl was covalently conjugated with the nanoparticle matrix, thus suppressing oxidative damage in the brain after reperfusion. t-PA and nitroxide radicals were confined and protected in the core of t-PA@iRNP, thereby preventing their rapid metabolism and excretion out of the body after systemic circulation for prolonged period. The nano-sized formulation prevented non-specific internalization of t-PA@iRNP in healthy cells, thereby preserving the normal function of redox reactions in the cells, especially important redox reactions such as electron transport chains. This improved pharmacological performance of t-PA@iRNP remarkably extended the in vivo half-life of t-PA in systemic circulation. Using a mouse model of photo-thrombotic middle cerebral artery occlusion, we found that t-PA@iRNP treatment, compared with naked t-PA, void iRNP, or t-PA@niRNP (non-ROS scavenging nanoparticle as a control), significantly suppressed increases in cerebral infarct volume and improved neurological deficit after brain ischemia. t-PA-induced subarachnoid hemorrhage was also suppressed by t-PA@iRNP treatment through elimination of overproduced ROS. Based on these data, t-PA@iRNP presents therapeutic potential through synergistic effect of thrombolysis and antioxidant effects for preventing and treating ischemia-reperfusion injury.